Effect of traditional Chinese Yijinjing exercise on hand dysfunction in rheumatoid arthritis patients: a randomized controlled trial - Chang, Tian; Ma, Xieli; Gong, Xun; Xia, Congmin; Jiang, Quan; Zhang, Rouman (Frontiers in Medicine, 2024)
Introduction: Rheumatoid arthritis (RA) patients often experience significant hand dysfunction. Yijinjing, a traditional Chinese exercise, has been recognized for its benefits to mind-body health. This study aimed to evaluate the efficacy and safety of Yijinjing in improving hand dysfunction among individuals with RA.Methods: This research was conducted as a single-center, outcome-blinded, randomized controlled trial. A total of 66 eligible RA participants were randomly assigned in a 1:1 ratio to either the Yijinjing exercise group (YJJG) with sessions conducted three times per week over a 12-week period or the control group (CG), which maintained ordinary activities. Various outcomes were assessed, including the Michigan Hand Outcomes Questionnaire (MHQ), handgrip strength, active range of motion (AROM), RA disease activity, the Health Assessment Questionnaire Disability Index (HAQ-DI), levels of anxiety and depression, and wrist ultrasound, all of which were collected at baseline and at the week 12.Results: At the end of the 12 weeks, the YJJG demonstrated significant improvements in MHQ scores compared to the CG (p < 0.05), alongside enhancements in handgrip strength and AROM, specifically in wrist extension, radial deviation, and metacarpophalangeal flexion (p < 0.05). Wrist ultrasound scores did not exhibit a significant increase in the YJJG, meaning no inflammation aggravation (p > 0.05). Additionally, morning stiffness duration, Disease Activity Score 28-ESR (DAS28-ESR), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) levels showed significant improvement in the YJJG (p < 0.05). Both groups reported enhancements in quality of life, as well as reductions in anxiety and depression scores, with the YJJG displaying greater improvements overall (p < 0.05). Importantly, no adverse events or significant abnormalities in vital signs were observed in either group.: Yijinjing exercise may effectively enhance hand function, grip strength, and flexibility in RA patients with low disease activity. Furthermore, it appears to improve quality of life and reduce anxiety and depression without exacerbating joint inflammation. 3 Clinical trial registration: [https://clinicaltrials.gov/study/NCT05527158], Identifier [NCT05527158].